2004
DOI: 10.4143/crt.2004.36.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic CDCA Derivatives-Induced Apoptosis of Stomach Cancer Cell Line SNU-1 Cells

Abstract: Purpose: This study was conducted to explore whether C D C A derivatives induce apoptosis in a stomach cancer cell line, and to dissect the detailed mechanism underlying apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…More and more evidences have indicated that CDCA (cell division cycle associated protein) is important in tumor evolution [ 5 , 6 ]. CDCA4 has been reported to be a potential biomarker for clinical outcome of osteosarcoma patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidences have indicated that CDCA (cell division cycle associated protein) is important in tumor evolution [ 5 , 6 ]. CDCA4 has been reported to be a potential biomarker for clinical outcome of osteosarcoma patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These agents have anti-tumor activity in gastric cancer, HCC, breast cancer, cervical cancer, prostate cancer, and T-cell leukemia. 99–104 …”
Section: Therapeutic Roles Of Bile Acid and Bile Acid Modulationmentioning
confidence: 99%
“…First, many researchers have shown that the UDCA derivatives HS-1030 and HS-1183, and the CDCA derivatives HS-1199 and HS-1200 induced apoptosis in various human cancer cells [22,[161][162][163][164][165][166][167][168][169][170][171]. HS-1030 is a form of UDCA conjugated with glycine methyl esters (Figure 3A,B).…”
Section: Cell Death Mechanism Of Synthetic Bile Acid Derivatives In C...mentioning
confidence: 99%
“…Treatment with synthetic bile acid derivatives (HS-1183, HS-1199, and HS-1200) reduced the levels of pro-caspase-3 and caspase-8 in Jurkat human leukemic T cells [161]. In addition, the levels of pro-caspase-3 were reduced in SNU-1 stomach cancer cells [165,166] and malignant glioblastoma cells (U-118MG, U-87MG, T98G, and U-373MG) [167]. Furthermore, HS-1200 decreased the levels of pro-caspase-3 and procaspase-7 in KAT-18 thyroid carcinoma cells [171].…”
Section: Cell Death Mechanism Of Synthetic Bile Acid Derivatives In C...mentioning
confidence: 99%